2017
DOI: 10.1097/md.0000000000005797
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities of different first-line chemotherapy regimens in the treatment of advanced ovarian cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Paclitaxel combined with carboplatin was recommended as a first-line chemotherapy strategy for ovarian cancer by National Institute for Health and Care Excellence, Scottish Intercollegiate Guidelines Network and National Comprehensive Cancer Network guidelines 1–3. Network meta-analyses have confirmed that paclitaxel plus carboplatin could improve progression-free survival (PFS) and overall survival (OS) compared with platinum alone 4 5. However, detailed implementation schedule (weekly or 3-weekly therapy) was not specified in these guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel combined with carboplatin was recommended as a first-line chemotherapy strategy for ovarian cancer by National Institute for Health and Care Excellence, Scottish Intercollegiate Guidelines Network and National Comprehensive Cancer Network guidelines 1–3. Network meta-analyses have confirmed that paclitaxel plus carboplatin could improve progression-free survival (PFS) and overall survival (OS) compared with platinum alone 4 5. However, detailed implementation schedule (weekly or 3-weekly therapy) was not specified in these guidelines.…”
Section: Introductionmentioning
confidence: 99%